(untitled) (Reflection and Critique Law Magazine, 2020)
This work was developed from the study of legal pluralism applied in large cities, in view of a great social inequality, especially not pointed to public safety where those who are resident in closed condominiums there is a greater concretion of the fundamental right to those who do not conditions financial resources to do so. From this perspective, it was proposed a possibility of popular participation for the implementation of public security policies in order to reduce crime and to achieve social pacification.